(untitled) (Latin-American Journal of Computing, 2019)
This document summarizes the design of a disaster recovery plan in the technology area for an insurance company in Ecuador. The first section sets out the legal, technical and project management frameworks; which are: the Codification of Insurance of Ecuador, the standard of the National Institute of Standards and Technology 800-34 and the management framework of the Project Management Institute, respectively. In the second section, the critical infrastructure and its recovery strategies are determined based on the processes of high criticality in impact analysis. As a result of the project management, the work breakdown structure, the risk matrix and the cost analysis are delivered; which will be important for the company to approve the execution of the project.